Shedding Light on the Extended Mind: HoloLens, Holograms, and Internet-Extended Knowledge - Smart, Paul R. (Frontiers in Psychology, 2021)
The application of extended mind theory to the Internet and Web yields the possibility of Internet-extended knowledge—a form of extended knowledge that arises as a result of an individuals interactions and engagements with the online environment. The present paper seeks to advance our understanding of Internet-extended knowledge by describing the functionality of a real-world application, called the HoloArt app. In part, the goal of the paper is illustrative: it is intended to show how recent advances in mixed reality, cloud-computing, and machine intelligence might be combined so as to yield a putative case of Internet-extended knowledge. Beyond this, however, the paper is intended to support the philosophical effort to understand the notions of extended knowledge and the extended mind. In particular, the HoloArt app raises questions about the universality of some of the criteria that have been used to evaluate putative cases of cognitive extension. The upshot is a better appreciation of the way in which claims about extended knowledge and the extended mind might be affected by a consideration of technologically-advanced resources.